Strategy of diabetes treatment - Basov, Igor; Švitra, Donatas; Vilkytė, Ramunė (Lietuvos matematikos rinkinys, 2010)
In this article the authors performed numerical analysis of glycemic regulation mathematical model described by two differential equations with one delay argument. The results obtained in the linear analysis [3] were used in numeric analysis constructing solutions applying the Runge-Kuto IV successive method in normal and diabetes cases. Diabetes medical strategy will be modeled to the above-mentioned model (2.1)–(2.2) introducing two external periodic functions determining food and exogenous insulin injections. Treatment strategy will be modeled applying a scientific simulation modeling program „Model Maker“.
Keywords: diabetes; glycemia; glycemic regulation; mathematical modelling of glycemia regulation; strategy of diabetes treatment